Capabilities and Performance of Early Internationalizing Firms: A Systematic Literature Review. (4th May 2023) - Jie, Shuijing; Harms, Rainer; Groen, Aard J.; Jones, Paul
ABSTRACT: International-entrepreneurship researchers use a capability-based perspective to analyze the international performance of early-internationalizing firms. More than 300 papers seem to address the role of capabilities in international performance. The purpose of this study is to structure this literature and provide an orientation for researchers. First, we develop a capability-categorization model. Second, we use this model in conjunction with our systematic literature review to identify which capabilities dominate the literature and which may have been overlooked. Third, we find that, in a significant share of the papers, "capability" is defined rather loosely, which impedes theory development at the interface of the capability-based perspective and international entrepreneurship. We conclude with a research agenda for future capabilities-based international-entrepreneurship research.